New potent αvβ3 integrin ligands based on azabicycloalkane (γ, α)-dipeptide mimics. Issue 12 (26th February 2016) - Pilkington-Miksa, M.; Araldi, E. M. V.; Arosio, D.; Belvisi, L.; Civera, M.; Manzoni, L.
Abstract : A novel promising integrin ligand based on an azabicycloalkane scaffold is able to inhibit both cell adhesion and migration without evidence of toxicity. Abstract : We have designed a new synthetic strategy for the preparation of a new class of cyclic RGD integrin ligands in which the azabicycloalkane scaffold can be envisaged as a (γ, α) dipeptide mimic. The synthesis and in vitro biological evaluation of these RGD derivatives, as well as the computational study of their conformational properties and binding modes to αV β3 integrin are described. Compound3 has shown to be a promising candidate as αV β3 integrin antagonist able to interfere with both cell adhesion and movement on vitronectin with no evidence of cytotoxic effects.